Non-invasive colonic imaging studies in inflammatory bowel disease - Alshammari, Meshari Turki (2024)
The global incidence of Inflammatory Bowel Disease (IBD) is rising, with current prevalence of 0.3%. Objective assessment of colonic inflammation is paramount for diagnosis, monitoring, and clinical management. Endoscopy is the gold standard for objective assessment of colonic disease activity in IBD. However, it has limitations; it requires bowel preparation, can be uncomfortable, is invasive and associated with rare but potentially serious risks such as perforation.